Analisis Komprehensif Lafaz Sharih Dan Kinayah: Makna, Penerapan Dalam Nash, dan Implikasi Hukumnya - Haq, Fitri Maylan; F, Fatmawati; Amin, Abd. Rauf (Media Hukum Indonesia (MHI), 2024)
The application of sharih and kinayah lafaz requires in-depth study because current developments require a re-examination of the meanings of lafaz in sharia texts so that they remain relevant to societal conditions, therefore this paper discusses the study of lafaz in terms of the use of sharih and knayah meanings. To obtain relevant research results, this research uses data collection techniques or literature study methods. The results of this research are that sharih and kinayah lafaz have contradictory meanings and applications, where sharih lafaz is a lafaz whose pronunciation and application is clear, does not require explanation and is not accompanied by intention, for example if the husband says "I am divorcing you with one divorce" without there is an intention in it, then the divorce still falls on the wife. Meanwhile, the lafaz kinayah is a lafaz which when pronounced has another meaning, namely that it must be explained, and accompanied by an intention, for example, a husband says to his wife, "Go home to your mother's house", then the meaning of these words is that the husband intends to return his wife to her parents, in other words, he wants to abandon his wife.